Assessing the impact of e-commerce of a footwear vendor in Malaysia through a structural equation modeling approach - Wan Nuraini Fahana Wan Nasir; Muhamad Safiih Lola; Abdul Aziz K. Abdul Hamid 1,2,*,; Sharifah Sakinah Syed Abd Mutal; Ribed Vianneca W. Jubilee 3 ,; Nurul Hila Zainuddin; Akhmad Fauzy (MDPI, 2024)
Businesses are leveraging digital technology through e-commerce platforms as a strategy to continue operating following the movement control order (MCO). Online shopping, a subset of e-commerce platforms, allows consumers to browse, select, and purchase products using digital interfaces. Unfortunately, there is a lack of understanding of how this platform can impact customer behavior. Therefore, this study aims to develop new knowledge of customer behavior and assess the relationship between consumer behavior and e-service quality in online shopping to better understand the e-service quality provided by the vendor in Malaysia. A novel model of e-service quality and consumer behavior has been developed and investigated. Survey questionnaires were distributed and tested using structural equation modeling (SEM) to 200 customers who had experienced online shopping during COVID-19. The finding revealed that website design, security/privacy, and fulfillment are statistically correlated with e-service quality. However, customer service is not significantly correlated with e-service quality. Meanwhile, the quality of e-services is statistically significantly related to customer behavior. This study shows that e-service quality can provide good customer behavior post-COVID-19. Online shopping is therefore predicted to boost the economy of the country, but consumers also want high-quality e-services to continue. Retailers can improve their storefronts, engage customers, and promote responsible consumption.